Combining ability studies in cucumber (Cucumis sativus L.) - Singh, Raghvendra; Singh, Anand Kumar; Kumar, Sanjay; Singh, BK; Singh, SP (Vegetable Science, 2011)
Combining ability effects were estimated for different characters of cucumber in a line x tester mating design comprising 12 lines and 3 testers and their 36 F1 hybrids. Parents and F1 crosses differed significantly for general combining ability and specific combining ability effects for all the characters respectively. The result revealed high and significant differences among the parents and hybrids for most of the characters except number node to male flower and female flower and length of fruit, indicating the importance of both additive and non-additive gene action. Among the parents, CC-5, BSC-1, and CC-7 were found to be good general combiner for number of primary branches per plant, weight per fruit, number of fruit per plant, fruit yield per plant etc. The cross combination VRC-18 x CC-5, BSC-1 x CC-5 and CC-7 x CHC-1 were found to be good specific combiner for fruit yield and its related contributing characters.